2017
DOI: 10.1111/jfb.13513
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vegetable shortening and cocoa butter as vehicles for cortisol manipulation in Salmo trutta

Abstract: This study demonstrates that vegetable shortening and cocoa butter are two effective vehicles for intraperitoneal cortisol implants in juvenile teleosts, specifically brown trout Salmo trutta, residing in north temperate freshwater environments. Each vehicle showed a different pattern of cortisol elevation. Vegetable shortening was found to be a more suitable vehicle for long-term cortisol elevation [elevated at 3, 6 and 9 days post treatment (dpt)], while cocoa butter may be better suited for short-term corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…The decline of oxazepam in the implants over time closely reflected the decline of oxazepam in fish tissues and plasma over time, where CO-implants and implanted fish showed more stable oxazepam levels, while oxazepam in VS-implants and implanted fish declined quickly across the exposure period (Table , Figure S3). Previously, Birnie-Gauvin et al noted that VS-implants released a higher dose of cortisol to fish tissues than cocoa butter (not tested here) and attributed this, in part, to the soft texture of VS at low temperatures. In this study, VS and CO implants were both pliable at low temperatures when removed during dissection (∼5–10 °C), but CO implants were firmer (McCallum, E., personal observations).…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…The decline of oxazepam in the implants over time closely reflected the decline of oxazepam in fish tissues and plasma over time, where CO-implants and implanted fish showed more stable oxazepam levels, while oxazepam in VS-implants and implanted fish declined quickly across the exposure period (Table , Figure S3). Previously, Birnie-Gauvin et al noted that VS-implants released a higher dose of cortisol to fish tissues than cocoa butter (not tested here) and attributed this, in part, to the soft texture of VS at low temperatures. In this study, VS and CO implants were both pliable at low temperatures when removed during dissection (∼5–10 °C), but CO implants were firmer (McCallum, E., personal observations).…”
Section: Resultsmentioning
confidence: 60%
“…For the means, any samples <LOQ were set to 1/2 the LOQ value (see Materials and Methods). Gauvin et al 30 noted that VS-implants released a higher dose of cortisol to fish tissues than cocoa butter (not tested here) and attributed this, in part, to the soft texture of VS at low temperatures. In this study, VS and CO implants were both pliable at low temperatures when removed during dissection (∼5−10 °C), but CO implants were firmer (McCallum, E., personal observations).…”
Section: Environmental Science and Technologymentioning
confidence: 65%
See 1 more Smart Citation
“…We evaluated the implants' performance over a month-long period by analyzing the concentrations of fluoxetine in muscle, brain, and plasma via liquid chromatography tandem mass spectrometry. Given previous research using similar lipid-based carriers (see McCallum et al, 2019 for oxazepam, andBirnie-Gauvin et al, 2018 for cortisol), we generally expected that fluoxetine concentrations would initially increase and then decline in all tissues over the month as fluoxetine migrates from the implant to the surrounding fish tissues down a concentration gradient. We also predicted that fluoxetine would bioconcentrate to the highest concentrations in brain tissues versus muscle and plasma because of its higher lipophilicity (Duarte et al, 2022).…”
Section: Introductionmentioning
confidence: 92%
“…Sham and cortisol treatments applied in 2014 were performed the same way except vegetable shortening (100% vegetable shortening, Crisco, OH, USA) was used as a vehicle. A validation study showed that exogenous manipulation of high doses of cortisol in vegetable shortening increased plasma cortisol to supraphysiological levels for 6 days post-treatment, and plasma cortisol was still elevated but at normal stress-induced physiological levels at day 9 post-treatment, but high doses of cortisol in cocoa butter only increased plasma cortisol to normal stress-induced physiological levels at day 3 and had no effect by day 6 (Birnie-Gauvin et al, 2018). Fooddeprived fish were kept in a pen placed in the stream for 14 days to reduce foraging opportunities, which resulted in a loss of mass (Midwood et al, 2016;Peiman et al, 2017).…”
Section: Tagging and Treatmentsmentioning
confidence: 99%